Antimicrobial drug resistant features of Mycobacterium tuberculosis associated with treatment failure - Mushtaq, Fizza; Raza, Syed Mohsin; Ahmad, Adeel; Aslam, Hina; Adeel, Atiqa; Saleem, Sidrah; Ahmad, Irfan (PloS one, 2023)
Tuberculosis stands as a prominent cause of mortality in developing countries. The treatment of tuberculosis involves a complex procedure requiring the administration of a panel of at least four antimicrobial drugs for the duration of six months. The occurrence of treatment failure after the completion of a standard treatment course presents a serious medical problem. The purpose of this study was to evaluate antimicrobial drug resistant features of Mycobacterium tuberculosis associated with treatment failure. Additionally, it aimed to evaluate the effectiveness of second line drugs such as amikacin, linezolid, moxifloxacin, and the efflux pump inhibitor verapamil against M . tuberculosis isolates associated with treatment failure. We monitored 1200 tuberculosis patients who visited TB centres in Lahore and found that 64 of them were not cured after six months of treatment. Among the M . tuberculosis isolates recovered from the sputum of these 64 patients, 46 (71.9%) isolates were simultaneously resistant to rifampicin and isoniazid (MDR), and 30 (46.9%) isolates were resistant to pyrazinamide, Resistance to amikacin was detected in 17 (26,5%) isolates whereas resistance to moxifloxacin and linezolid was detected in 1 (1.5%) and 2 (3.1%) isolates respectively. Among MDR isolates, the additional resistance to pyrazinamide, amikacin, and linezolid was detected in 15(23.4%), 4(2.6%) and 1(1.56%) isolates respectively. One isolate simultaneously resistant to rifampicin, isoniazid, amikacin, pyrazinamide, and linezolid was also identified. In our investigations, the most frequently mutated amino acid in the treatment failure group was Serine 315 in katG . Three novel mutations were detected at codons 99, 149 and 154 in pncA which were associated with pyrazinamide resistance. The effect of verapamil on the minimum inhibitory concentration of isoniazid and rifampicin was observed in drug susceptible isolates but not in drug resistant isolates. Rifampicin and isoniazid enhanced the transcription of the efflux pump gene r v1258 in drug susceptible isolates collected from the treatment failure patients. Our findings emphasize a high prevalence of MDR isolates linked primarily to drug exposure. Moreover, the use of amikacin as a second line drug may not be the most suitable choice in such cases.